Periodicals Received (Review of Economic Studies, 1941)
Journal Article Periodicals Received Get access The Review of Economic Studies, Volume 8, Issue 3, June 1941, Page 188, https://doi.org/10.2307/restud/8.3.188-a Published: 01 June 1941